The effect of fennel seeds on pH of saliva - A clinical study - Rajkumar Manohar; Akila Ganesh; N Abbyramy; R Abinaya; S K Balaji; S Banu Priya (Wolters Kluwer Medknow Publications, 2020)
Context: Saliva is an oral fluid that gives a protective effect against dental caries. Chewing of fennel seeds after food is a common culture in the Indian Sub-continent. A review of previous studies on fennel seeds showed that some of them have an anti-microbial efficacy, but there are no extensive data available on the effect of chewing fennel seeds on the pH of saliva. Aim: The aim of the study was to record the baseline pH of saliva and to record the changes in salivary pH after chewing fennel seeds. Setting and Design: The study was carried out in the Department of Public Health Dentistry, Sri Ramachandra University, Chennai, prior to which a pilot study was carried out. Subjects and Methods: Voluntary enrolment of 30 individuals was done. A written and informed consent was obtained from the individuals prior to the study. The pH of the saliva was recorded by placing the standardized salivary strip below the tongue in the oral cavity and colour changes were matched with the pH scale colour chart within about 15 sec. The subjects were asked to chew fennel seeds for 5 min. Salivary pH was measured immediately after chewing (SP2) at 0 min and the experiment was repeated for 5 min (SP3), 10 min (SP4), 15 min (SP5) and 30 min (SP6). Statistical Analysis: The data was gathered and analysed using paired t test. Results: There was an increase in salivary pH from baseline (SP1) to 0 min (SP2) was found to be highly significant (P = 0.000). The mean salivary pH reduced to 7.64 ± 0.06, 5 min after chewing the seeds (SP3) and the drop in pH was found to be highly significant (P = 0.000). The subsequent drop in pH from 10 min (SP4), 7.50 ± 0.05 to 15 min (SP4), 7.38 ± 0.05 to 30 min (SP4), 7.24 ± 0.05 were found to be highly significant as well (P = 0.000). Conclusion: Chewing of fennel seeds increases the pH of saliva, thus making it a suitable anti-cariogenic agent.